Kriteria Pemimpin dalam Al-Qur’an dan Aplikasinya pada Masyarakat Kemukiman Lamgarot Aceh Besar - Muhammad Zaini; Nurlaila Nurlaila; Nurshadiqah Fiqria (TAFSE: Journal of Qur'anic Studies, 2021)
Every human being is a leader and will be held accountable for his leadership. In this discussion, the intended leader is someone who is favored and elected by the community to assume the scepter or leadership in a certain area. In this case, the Qur'an has explained several criteria in choosing a leader. However, people do not pay much attention to these criteria when choosing leaders. This discussion will focus on the extent of understanding of the Lamgarot community regarding the criteria for leaders and their application in selecting and determining leaders. The author finds that the criteria for a leader mentioned in the Qur'an are Islam (QS. al-Ma`idah (5): 51, fair and trustworthy (QS. al-Nisa` (4): 58, and strong (QS. al -Qashash (28): 26. In general, the people of the Lamgarot Village understand the criteria for leadership as described in the Qur'an, but only a few people have applied their understanding in practical ways. Setiap manusia adalah pemimpin dan akan dimintai pertanggungjawaban atas kepemimpinannya. Dalam pembahasan ini, pemimpin yang dimaksudkan adalah seseorang yang diunggulkan dan dipilih oleh masyarakat untuk memangku tongkat kekuasaan atau kepemimpinan di dalam wilayah tertentu. Dalam hal ini, al-Qur`an sudah memaparkan beberapa kriteria dalam memilih pemimpin. Akan tetapi, masyarakat tidak terlalu memerhatikan kriteria tersebut ketika memilih pemimpin. Pembahasan ini akan berfokus pada sejauhmana pemahaman masyarakat Kemukiman Lamgarot mengenai kriteria pemimpin serta aplikasinya dalam memilih dan menentukan pemimpin. Penulis menemukan kriteria pemimpin yang disebutkan dalam al-Qur`an adalah Islam (QS. al-Ma`idah (5): 51, adil dan amanah (QS. al-Nisa` (4): 58, dan kuat (QS. al-Qashash (28): 26. Secara garis besar, masyarakat Kemukiman Lamgarot sudah memahami kriteria pemimpin seperti yang dijelaskan di dalam al-Qur`an. Hanya saja, dari segi aplikasinya, baru sebagian masyarakat yang menerapkan pemahaman mereka.